Sharia Financial Literacy of UMS MSMEs Related to Sharia Bank Financing Products - Nazri, Hasib; Hakim, Lukmanul (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine the level of understanding and application of Islamic financial literacy in Micro, Small, and Medium Enterprises (MSMEs) around the University of Muhammadiyah Surakarta (UMS) Campus in utilizing Islamic bank financing products. MSMEs have a strategic role in the national economy, but the level of Islamic financial literacy in Indonesia in general is still lagging behind conventional finance. Methodology: The research method used is qualitative descriptive. Data was collected through in-depth interviews, observations, and documentation of 15 MSME actors engaged in various fields, especially culinary. The sampling technique was carried out by purposive sampling and data analysis using the Miles, Huberman, and Saldaña models which included data reduction, data presentation, and conclusion drawn. Results: The results of the study show that the level of sharia financial literacy of MSME actors around UMS is still relatively low. In terms of knowledge, the majority of respondents were in the category of Not Literate (46.7%) and Less Literate (40.0%). In terms of financial behavior, most respondents (66.7%) are in the Less Literacy category. Regarding access to financing, as many as 60.0% of respondents were in the Not Literate category, which showed a major obstacle in reaching Islamic banking products due to a lack of understanding of the product and how to apply. This study concludes the need for more active and innovative socialization from Islamic banking to increase the literacy and interest of MSME actors in sharia financing products.